Using Twitter to increase content dissemination and control educational content with Presenter Initiated and Generated Live Educational Tweets (PIGLETs). (3rd July 2017) - Tomlinson, Sarah; Haas, Mary; Skaugset, L. Melissa; Cico, Stephen J.; Wolff, Margaret; Santen, Sally; Lin, Michelle; Huang, Robert
Abstract: Live-tweeting during educational presentations is typically learner-generated and can lead to misquoted information. Presenter curated tweets have not been well described. We created Presenter Initiated and Generated Live Educational Tweets (PIGLETs) with the goal to broaden the reach of educational conferences. We hypothesized that using PIGLETs would increase the reach and exposure of our material. We developed a prospective single-arm intervention study performed during the "Not Another Boring Lecture" workshops presented at two national conferences in 2015. Presenters tweeted PIGLETs linked to unique hashtags #NotAnotherBoringLecture and #InnovateMedEd. Analytic software was used to measure the following outcomes: (1) number of tweets published by presenters versus learners, (2) reach (users exposed to content containing the hashtag), and (3) exposure (total number of times content was delivered). One hundred and twenty-six participants attended the workshops. A total of 636 tweets (including retweets) were sent by presenters containing the study hashtags, compared with 162 sent by learners. #NotAnotherBoringLecture reached 47, 200 users and generated 136, 400 impressions; #InnovateMedEd reached 36, 400 users and generated 79, 100 impressions. PIGLETs allowed presenters to reach a significant number of learners, as well as control the content delivered through Twitter. PIGLETs can be used to augment educational sessions beyond the physical confines of the classroom.